2019
DOI: 10.2478/hacq-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Kurgan Database – a citizen science tool for conserving grasslands on historical sites

Abstract: Eurasian steppes have an essential role in conserving biodiversity, but due to the huge habitat loss in the past centuries they are often preserved only in small refuges. Among such refuges are the ancient steppic burial mounds (the so called ‘kurgans’) which have a high cultural and historical importance and are also essential sites of nature conservation. Despite their high number (approximately half million) and conservational importance there is a huge lack of knowledge on the locality and conservational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
17
0
3
Order By: Relevance
“…This special issue consists of five contributions, from Switzerland , Hungary (Deák et al 2019, Greece (Tsiobani et al 2019), and Ukraine (Polchaninova et al 2019). These studies cover a wide range of grassland ecosystems from mountain dry grasslands to lowland loess grasslands, feather-grass steppes and wet grasslands, and focus on the biodiversity value and conservation issues of Palaearctic grasslands.…”
Section: Contributions Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This special issue consists of five contributions, from Switzerland , Hungary (Deák et al 2019, Greece (Tsiobani et al 2019), and Ukraine (Polchaninova et al 2019). These studies cover a wide range of grassland ecosystems from mountain dry grasslands to lowland loess grasslands, feather-grass steppes and wet grasslands, and focus on the biodiversity value and conservation issues of Palaearctic grasslands.…”
Section: Contributions Of the Special Issuementioning
confidence: 99%
“…The authors showed that the "Stipo-Poion" of Swiss authors consists of two floristically and ecologically distinct units belonging to the Stipo pulcherrimae-Festucetalia pallentis and the Festucetalia valesiacae orders. A new database on the conservation values associated with the ancient steppic burial mounds, is introduced in the paper of Deák et al (2019). Kurgans are ancient burial mounds built by nomadic steppic cultures dating back to the Bronze Age.…”
Section: Contributions Of the Special Issuementioning
confidence: 99%
“…Other types of SNFs have religious or cultural importance, which prevented their agricultural utilisation (Dudley et al 2009;Molnár V. et al 2017;Löki et al 2019). Amongst them, ancient burial mounds (also called kurgans) of the Eurasian steppe and forest steppe regions are of particular importance (Sudnik-Wójcikowska et al 2011;Bede et al 2015;Bede and Csathó 2019;Deák et al 2016aDeák et al , 2019Dembicz et al 2018). They are earthen mounds of a few metres height, which were constructed from the topsoil layers of the surrounding areas by nomadic steppic tribes several millennia ago, mainly for burial purposes (Dembicz et al 2016;Lisetskii et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are earthen mounds of a few metres height, which were constructed from the topsoil layers of the surrounding areas by nomadic steppic tribes several millennia ago, mainly for burial purposes (Dembicz et al 2016;Lisetskii et al 2016). The estimated number of these mounds is more than 600,000 in Eurasia and they are typical landscape elements from Hungary to Mongolia (Deák et al 2016a(Deák et al , 2019. A considerable proportion of these mounds still hold grassland vegetation; hence, mounds are valued as being stepping stones or biodiversity hotspots for grassland specialist plant and animal species even in transformed agricultural landscapes (Bede and Csathó 2019;Tóth et al 2019;Deák et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Almost half a million ancient burial mounds, with heights of 3-12 meters, are located in the Eurasian steppe and forest steppe zones (Deák et al 2016a(Deák et al , 2019. These mounds were predominantly built for burial purposes from the Late Neolithic to the Early Middle Ages (4500 BC -900 AD).…”
Section: Introductionmentioning
confidence: 99%